The Effectiveness of Management Information Systems (MIS) and its impact on Governmental Organization Performance in Jouf Region of Saudi Arabia - يحيى عبد الرحيم الشاذلي; احمد بدر الدين محمد; عبد الرحمن حمزة عبد الله; علي ابو ذر يوسف (Journal of Economics and Administrative Sciences, 2019)
The aim of this research is to find the impact of the efficiency of Management information systems (MIS) on the effectiveness of governmental organizations performance. To achieve the objective of the research, the analytical descriptive method was adopted. A questionnaire was designed consisting of (35) paragraphs, and the sample consisted of (200) individual. The research attemped to answer the following question: To achieve the objective of the research, the analytical descriptive method was adopted. A questionnaire was designed consisting of (35) paragraphs, and the sample consisted of (200) individual. The research tried to answer the following question: What is the actual utilization of modern administrative systems in focusing on auditors, Creativity and innovation, efficient operations and quality of service provided by government organizations. The results of the research indicate that: The effectiveness of management information systems leads to increased attention and focus on the auditors as well as increase the creativity and innovation in government organizations in addition to their positive impact on the efficiency of operations and the quality of services provided by governmental organizations in Jouf region of Saudi Arabia.